Impacto de un traductor virtual móvil a lenguaje de señas peruana en la comunicación alternativa de sordos en la ciudad de Iquitos 2024 - Panduro Vela, Abel Alexander (2025)
he present thesis research work sought to identify the impact of a mobile application translating voice and text into Peruvian Sign Language (LSP) on the alternative communication of the deaf in the city of Iquitos during 2024, for this purpose a question was posed research to what is the impact of a mobile virtual translator into Peruvian sign language on the alternative communication of the deaf in Iquitos in 2024. The summer population constituted by deaf people from the city of Iquitos and the sample by deaf people registered in the alternative basic education centers (CEBA) under the restriction of the inclusion and exclusion criteria proposed to obtain better results. The research was a non experimental, applied, quantitative and analytical intervention that sought to document the greatest amount of relevant information to determine the impact. Keyword: Interpreter, Peruvian Sign Language, deaf.